2015
DOI: 10.1093/jmammal/gyv113
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of life-history parameters between free-ranging and captive killer whale (Orcinus orca) populations for application toward species management

Abstract: Data collected on life-history parameters of known-age animals from the northern (NR) and southern resident (SR) killer whales (Orcinus orca) of the eastern North Pacific were compared with life-history traits of killer whales located at SeaWorld (SEA) facilities. For captive-born SEA animals, mean age and body length at 1st estrus was 7.5 years and 483.7cm, respectively. Estimated mean age at 1st conception was different (P < 0.001) for the combined data from both northern and southern resident (NSR) free-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 73 publications
(121 reference statements)
2
36
0
Order By: Relevance
“…For instance, even if we take a much more conservative approach that only includes captive born animals that have lived beyond 30 d of age (while still recognizing that a bias against captive born animal survival rates will result), a Kaplan‐Meier analysis (Stata Statistical Software: Release 13; StataCorp, College Station, TX) reveals the median life expectancy (MLE) changes from the 14.1 yr value reported by Jett and Ventre () for captive born killer whales to 21 yr. A MLE of 21 yr is not significantly different than the MLE of 20.1 yr found for the southern resident killer whale populations of the Pacific Northwest (Robeck et al . ).…”
Section: Kaplan‐meier Predicted Survival To Age Milestones For Captivmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, even if we take a much more conservative approach that only includes captive born animals that have lived beyond 30 d of age (while still recognizing that a bias against captive born animal survival rates will result), a Kaplan‐Meier analysis (Stata Statistical Software: Release 13; StataCorp, College Station, TX) reveals the median life expectancy (MLE) changes from the 14.1 yr value reported by Jett and Ventre () for captive born killer whales to 21 yr. A MLE of 21 yr is not significantly different than the MLE of 20.1 yr found for the southern resident killer whale populations of the Pacific Northwest (Robeck et al . ).…”
Section: Kaplan‐meier Predicted Survival To Age Milestones For Captivmentioning
confidence: 97%
“…, Robeck et al . ) are illustrated in Table . It should be noted that for statistical comparison it is necessary to meet the assumption that all individuals have the same survival probability.…”
Section: Kaplan‐meier Predicted Survival To Age Milestones For Captivmentioning
confidence: 99%
“…In the other 2015 study 1 , researchers led by SeaWorld veterinary surgeon Todd Robeck came to a very different conclusion: that animals now in captivity at SeaWorld's US parks live just as long as wild populations. The researchers looked only at animals held at those parks after 2000, and produced a survival rate that is higher than a rate that they calculated for southern…”
mentioning
confidence: 99%
“…More recent research, comparing the mortality rates of captive and wild Killer whales, indicated that they have similar life expectancies (Robeck et al ., ), although Jett & Ventre () reanalysed the data in this study and showed that although survival has improved it is still below that found in the wild. However, longevity is a crude and not very meaningful measure of success, especially if the Killer whales in zoological institutions have a poor quality of life.…”
Section: Introductionmentioning
confidence: 74%